Indeks Aktivitas Literasi Membaca Peserta Didik Dan Prestasi Akademik: Studi Korelasi Pada 34 Propinsi Di Indonesia - Agustina Agustina (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
The Indonesian government's efforts to eradicate illiteracy deserve appreciation, but this has not been accompanied by successful efforts in building a reading culture in the community. This is in accordance with various world surveys that note the low level of literacy in Indonesia. There are several studies through quantitative studies on interest and fondness for reading in various provinces in Indonesia, and this can be used as comparison material. One of the comprehensive studies conducted by the Center for Policy Research on Education and Culture, Research and Development Agency, Ministry of Education and Culture released the Reading Literacy Activity Index (Alibaca Index) in 34 provinces in Indonesia. Seeing this data, what becomes interesting to study later is whether the reading literacy level has a correlation with the student's academic achievement variable. This is important because in the end the school/madrasah literacy movement is aimed at achieving the highest level that goes beyond the level of habituation and development, namely the level of learning. This study aims to answer the questions, 1) Is there a significant positive correlation between students' reading literacy levels and academic achievement, in 34 provinces in Indonesia? and 2) What strategies should schools/madrasahs do to increase students' reading literacy levels and at the same time increase the achievement of academic achievement? This study uses a descriptive correlational approach by collecting data through the study of documentation and interviews. The results showed that the correlation between reading activity index and academic achievement (r) was 0.766. There are several innovation ideas also described qualitatively as a result of interviews.